PENGELOLAAN SARANA DAN PRASARANA PROMOSI DALAM MENUNJANG EFEKTIVITAS STRATEGI PROMOSI DAERAH DI KABUPATEN INDRAGIRI HILIR - jurnalmap map; Winda Altra Sarjana; Indra Prasetyo; Sri Mulyani (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2021)
This study is to analyze how the management of promotional facilities and infrastructure in supporting the effectiveness of regional promotion strategies in Indragiri Hilir Regency. The background of this research is to find out a more in-depth study to analyze the increase in investment realization through the promotion of strategies carried out by the Indragiri Hilir Regency Government, by carrying out the management of promotional facilities and infrastructure to attract investors to invest in Indragiri Hilir Regency, whose ultimate goal is is so that the economic growth and welfare of local communities can compete with other regions, taking into account the support for the management of promotional facilities and infrastructure in supporting the effectiveness of regional promotion strategies in Indragiri Hilir Regency. The research was conducted using qualitative research, which aims to gain a general understanding of social reality from the perspective of the participants who are the focus of the research. The results showed that the management of facilities and promotion of infrastructure supporting the effectiveness of regional promotion strategies in Indragiri Hilir Regency was not effective in terms of management functions, namely planning, organizing, implementing and controlling.